The Effectiveness of Training on Managing Public Employee Performance - A Field Study at the Ministry of Commerce Branches in Makkah Region - - Al-Jobairi, Naif; Taibah, Hassan; Jifri, Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed to discover the effectiveness of training on managing public employee performance. The research presents the main training stages and their ability to adopt the new variable ’performance management’ and apply its processes in government agencies and establish a culture of performance in general among employees. This is going to be achieved through conducting a field study in the Ministry of Trade branches in Makkah region. The study assumed a positive relationship with a statistical significance at the level of (0.05) between the effectiveness of training for the public employee and the ability to formulate smart goals, and understanding merits, and information stability. The research adopted the analytical quantitative approach, whereby the questionnaire was sent to the entire study population consisting of (395) employees in Makkah branches, and (95) responded (24.05%). The relationship between variables was then tested using Pearson correlation coefficient and linear regression analysis. The main results of the study clarify the relationship between training fundamentals on one hand, and the employees’ acquisition of formulating goals and understanding the new performance management system on the other hand. Therefore, researchers recommend designing programs for state employees to aim for introducing performance management, which will contribute to their knowledge and participation abilities. The researchers also pointed out the unique experience of the Ministry of Commerce in performance management training as a successful example that should be followed by other public entities.